PERAN PERMAINAN TRADISIONAL BAKIAK DALAM MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK USIA 3-4 TAHUN - Endang Puspitasari; Siti Nurkholishoh; Umu Da'watul Choiro (Nahdlatul Ulama University Sunan Giri Bojonegoro, Indonesia, 2022)
This study aims to determine the role of the traditional game of clogs in improving the gross motor skills of children aged three to four years. Clogs is a traditional game in West Sumatra, this game uses a type of sandal whose soles are made of wood and foot straps made of tires that are nailed on both sides. Using descriptive qualitative research methods. The research was conducted in the Playgroup of Al Sains Maindu Montong Tuban, using the research subjects who were the children of the playgroup. Data collection is done by conducting observations or observations, interviews and documentation. Data analysis is done by providing an explanation of the data that has been collected. Data analysis using triagulation technique. the results of research that has been carried out on children playing groups. Gross motoric skills of children increased in this study through the traditional game process of clogs. the child is able to lift the clogs, the child is able to move the clogs from one step to the next, the child is able to walk the specified distance and the child is able to pass obstacles well in the game of clogs.